THE IMPACT OF UNDERSTANDING OF RIBA ON THE USE OF ISLAMIC FINANCIAL INSTITUTIONS SERVICES: RESEARCH IN SADANANYA DISTRICT, CIAMIS REGENCY - Maya Puspitasari; Hammad Mutawakil Hibatillah (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2022)
This study aims to determine the effect of understanding usury on the use of Islamic financial institutions in Sadananya District, Ciamis Regency. With a sample of 45 people, this study adopted a quantitative approach based on regression analysis. The results showed a high understanding of usury in the Muslim community of Sadananya District, Ciamis Regency. An understanding of usury is proven to affect the use of Islamic financial institutions, as indicated by the results of the significant test calculation of the correlation coefficient at a significant level of 5%, the t-count value is 3.840 while the t-table is 2.01669, and the significance level is 0.000 < 0.05. Thus it can be concluded that the null hypothesis is rejected and the working hypothesis is accepted. The influence of the variable understanding of usury on the use of the services of Islamic financial institutions is 25.5%, while other variables influence the remaining 74.5%.